Circulating biological markers in prediction of clinical outcomes in patients with chronic heart failure - А. А. Kremzer (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of this study was the creation of an evaluation cardiovascular risk score, based on an analysis of circulating biomarkers of CHF.